Scandal of Sacramentality The Eucharist in Literary and Theological Perspectives. - Hancock, Brannon (Cambridge : James Clarke & Co, 2014)
In this new book, Brannon Hancock explores the theme of the ""scandalous"" sacrament in the context of our current Western culture which some would describe as ""post-Christian"", and in the light of the Christian churches who hold sacramental life as central to their faith.In the texts addressed by Hancock we return to the body in all its messy complexity, and therefore to the mystery which lies at the very heart of the sacramental incarnation, the Word made Flesh.
Front cover; Title page; Copyright; Contents; Foreword by Ann Loades; Foreword by David Jasper; Acknowledgments; Introduction; Part One: The Scandal of Sacramentality; 1. Skandalon: Stumbling over Sacrament; 2. ""The Word . . ."": The Problem of Language; 3. "". . . Made Flesh"": The Problem of the Body; Part Two: Literary and Theological Perspectives; 4. Fracturing: Brokenness and Sacrament; 5. Consuming: Cannibalism and Sacrament; 6. Penetrating: Eroticism and Sacrament; Conclusion: In-Conclusion; Bibliography; Back cover
Description based upon print version of record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Lord's Supper -- Catholic Church; Human body -- Religious aspects; Christianity and literature; Christianity and the arts; RELIGION / Christian Theology / Soteriology; Christianity and literature; Christianity and the arts; Human body -- Religious aspects; Lord's Supper -- Catholic Church; RELIGION / Christian Rituals & Practice / Sacraments; Electronic books